Substituted pyrazinecarboxamides: synthesis and biological evaluation - Doležal, Martin; Palek, Lukáš; Vinšová, Jarmila; Buchta, Vladimír; Jampílek, Josef; Kráľová, Katarína (Molecules, 2006)
Condensation of the corresponding chlorides of some substituted pyrazine-2-carboxylic acids (pyrazine-2-carboxylic acid, 6-chloropyrazine-2-carboxylic acid, 5-tert-butylpyrazine-2-carboxylic acid or 5-tert-butyl-6-chloropyrazine-2-carboxylic acid) with various ring-substituted aminothiazoles or anilines yielded a series of amides. The syntheses, analytical and spectroscopic data of thirty newly prepared compounds are presented. Structure-activity relationships between the chemical structures and the anti-mycobacterial, antifungal and photosynthesis-inhibiting activity of the evaluated compounds are discussed. 3,5-Bromo-4-hydroxyphenyl derivatives of substituted pyrazinecarboxylic acid, 16-18, have shown the highest activity against Mycobacterium tuberculosis H(37)Rv (54-72% inhibition). The highest antifungal effect against Trichophyton mentagrophytes, the most susceptible fungal strain tested, was found for 5-tert-butyl-6-chloro-N-(4-methyl-1,3-thiazol-2-yl)pyrazine-2-carboxamide (8, MIC =31.25 micromol x mL(-1)). The most active inhibitors of oxygen evolution rate in spinach Molecules 2006, 11,243 chloroplasts were the compounds 5-tert-butyl-6-chloro-N-(5-bromo-2-hydroxyphenyl)- pyrazine-2-carboxamide (27, IC(50) = 41.9 micromol x L(-1)) and 5-tert-butyl-6-chloro-N-(1,3- thiazol-2-yl)-pyrazine-2-carboxamide (4, IC50 = 49.5 micromol x L(-1)).
Keywords: Amides; pyraziny; Structure-Activity Relationship; kyseliny karboxylové; antifungální látky; Financing, Organized; financování organizované; Carboxylic Acids; antibakteriální látky; Anti-Bacterial Agents; Pyrazines; vztahy mezi strukturou a aktivitou; Antifungal Agents; Photosynthesis; Mycobacterium tuberculosis; fotosyntéza; amidy